The Junior Dansnotators. Issue 2 (3rd April 2019) - Hutchinson Guest, Ann
ABSTRACT: This article details my experiences developing and running the Junior Dansnotators program at the Dance Notation Bureau in New York City from 1957 to 1961. The programming for the students included classes in various dance techniques, classes in Labanotation, discussions, repertory readings from Labanotation, choreography, social gatherings, and attending performances. Each of these components is discussed, including supporting statements from the Junior Dansnotators themselves.